The Effectiveness of Using Animated Video Learning Media on Students' Pronunciation Mastery at SMP Negeri 11 Banda Aceh - El Sukny, Munawar; Yusnida, Dara; Ayouni, Nour (Program Studi Pendidikan Bahasa Inggris, FKIP - Universitas Iskandar Muda, 2023)
This research aimed to determine the effectiveness of animated video learning media on students' pronunciation mastery at SMP Negeri 11 Banda Aceh. The researcher used quasi-experimental research where the data was gained from oral tests. The study population was the ninth-grade students of SMP Negeri 11 Banda Aceh in the academic year 2022/2023. The sample was taken by using a purposive sampling technique. There were 226 students as population and 42 students as sample, the total number of students from the experimental and control classes. The results showed that the mean score of students' pronunciation mastery in the practical class was 36.66, becoming 82.05, with a 124% improvement. Then, the mean score of students' pronunciation mastery in the control class was 44.86, becoming 55, with a 23% improvement. Both classes have the same initial classification: poor (36-55). In the experimental class, there was an improvement in qualifications from poor (36-55) to good (76-85), while in the control class, there was no improvement in capabilities which was still in poor (36-55). The t-test analysis was presented by applying a 0.05 level of significance with the 20 degrees freedom (df=21-1); the t-test value in the experimental class was more significant than the t-table (14.63>2.080), and in the control class, the t-test value was also greater than t-table (5.61>2.080). Based on the results, animated video learning media significantly affects students' pronunciation mastery.